Amyloidogenic occipital mass obscuring plasmacytoma: a rare presentation and review of literature - Verma, Tripti; Srivastava, Pallavi; Awasthi, Namrata P.; Kaif, Mohd.; Husain, Nuzhat (International Journal of Research in Medical Sciences, 2024)
Solitary plasmacytoma of bone are a spectrum of plasma cell disorder which are defined by presence of clonal plasma cell in the bone including skull. The occurrence of true plasmacytoma of skull with large amyloid deposits in young patient is a rare presentation. We present case of 25-year-old man with a 3-month history of a slowly growing mass in the occipital region associated with headache. Neurological examination was within normal limits. Magnetic resonance imaging revealed a large extra-axial mass, the inner table of the skull were partially destroyed by the tumour, but the dura was not involved. The tumour removed and the skull defect was reconstructed followed by radiotherapy. Histopathological examination confirmed plasmacytoma with amyloidosis, positive for amyloid P component on immunohistochemistry. Laboratory investigations revealed no systemic myelomatosis. After 2 years of close follow up patient had no signs of recurrence or progression to multiple myeloma. The different management stratagies for the two entities of plasma cell disorder spectrum i.e. solitary plasmacytoma of bone and multiple myeloma necessitates there differentiation by thorough clinical, radiological and hematological studies. Surgical treatment followed by radiotherapy is an effective treatment option.